2008
DOI: 10.1002/jbm.a.32058
|View full text |Cite
|
Sign up to set email alerts
|

Titanium oxide as substrate for neural cell growth

Abstract: Titanium oxide has antiinflammatory activity and tunable electrochemical behavior that make it an attractive material for the fabrication of implantable devices. The most stable composition is TiO2 and occurs mainly in three polymorphs, namely, anatase, rutile, and brookite, which differ in its crystallochemical properties. Here, we report the preparation of rutile surfaces that permit good adherence and axonal growth of cultured rat cerebral cortex neurons. Rutile disks were obtained by sinterization of TiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 44 publications
5
39
0
Order By: Relevance
“…Proximal location of materials coated with picometer to micrometer titanium particles reduced the resting membrane potential and action potential firing rate of pyramidal neurons [3] and increased alkaline phosphatase activity, mineral deposition, and bone-related gene expression in osteoblast cells [4]. These in vitro outcomes were consistent with other work showing titanium or titanium-coated materials to have anti-inflammatory and antioxidant effects, and promote nerve cell growth [5,6,7,8]. In humans, garments and tape permeated with Aqua Titan particles restored Achilles tendon stiffness and enhanced the short latency reflex response [9] with subsequent improvement in running economy [10] during recovery from strenuous hill running exercise in male athletes.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Proximal location of materials coated with picometer to micrometer titanium particles reduced the resting membrane potential and action potential firing rate of pyramidal neurons [3] and increased alkaline phosphatase activity, mineral deposition, and bone-related gene expression in osteoblast cells [4]. These in vitro outcomes were consistent with other work showing titanium or titanium-coated materials to have anti-inflammatory and antioxidant effects, and promote nerve cell growth [5,6,7,8]. In humans, garments and tape permeated with Aqua Titan particles restored Achilles tendon stiffness and enhanced the short latency reflex response [9] with subsequent improvement in running economy [10] during recovery from strenuous hill running exercise in male athletes.…”
Section: Introductionsupporting
confidence: 75%
“…Aqua Titan, when integrated into a tape applied to the skin, also proved to be non-toxic to neuronal tissue [3]. TiO 2 -rutile cultures showed good survival of CNS neurons, with typical development of axons [5]. Together, these data suggest a potential use for titanium in CNS implants.…”
Section: Neural Responsementioning
confidence: 99%
“…First cell cultures were carried out over TiO 2 -rutile dense samples covered with a solution of poly-l-lysine (PLL). Results showed that TiO 2 as rutile phase permits good survival of mammalian CNS neurons for at least 10 days in culture (39). Neurons generally extended axons with normal appearance but they had few and short dendrites with some differences being observed in relation with the temperature of annealing of the surfaces.…”
Section: Canillas B Moreno-burriel E Chinarromentioning
confidence: 97%
“…Ti has superior biocompatibility and its oxide is used in medical care for example as implants. 36 Thus, the evaluation of the neuronal affinity to different materials can lead to the optimization of neuronal growth scaffolds using nano-structures. Figure 6 shows SEM (A, C) and fluorescent (B, D) images of neurons cultivated on Au (A, B) and Ti (C, D), respectively.…”
Section: Evaluation Of Neuronal Affinity and Growth With Differentmentioning
confidence: 99%